Milk yield and some milk quality traits of akkaraman, bafra and bafra x akkaraman f1 sheep - Mücahit Kahraman; Banu Yüceer Özkul (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate milk yield and some milk quality traits, of Akkaraman (Akk), Bafra (Baf) and Bafra x Akkaraman (F1) sheep. Materials and Methods: The research was carried out at Gözlü State Farm. A total 75 head Akkaraman, Bafra ve Bafra x Akkaraman F1 cross sheep have been used as animal material in the study. Results: The overall means in sheep from Akk, Baf and F1 were detected as 683,61±30,08; 849,76±55,63 and 753,17±54,90 g for daily milk yield; 99,57; 126,40 and 112,52 kg for milk yield; 133,12; 135,84 and 133,80 day for lactation duration respectively. The highest daily milk yields was assesed on 45th day of lactation period. The overall means in sheep from Akk, Baf and F1 were found as %5,85; 5,44 and 5,67 (P>0,05) for fat rate; %5,09; 5,02 and 5,03 (P>0,05) for protein rate; %4,89; 5,04 and 5,02 (P>0,05) for lactose rate; %16,81; 16,42 and 16,67 for dry matter rate; 275,46; 216,48 and 258,86 x103/ml (P>0,05) for somatic cell count respectively. Conclusion: It was determined that the crossing study of Bafra x Akkaraman F1 genotype sheep showed positive results in terms of milk yield. Milk yield traits of cross genotype was good level and its milk quality was appropriate to the values reported for sheep milk. According to these results, it can be said that the new genotype should be used in milk yield and lamb production.